Green Innovation Is An Approach To Achieving Environmental Sustainability - With A Presentation Of Some Experiences - Bellakhdar, Messaouda (جامعة الوادي - University of Eloued, 2022)
Developments in the last decade have led to serious discussions about the environmental problems experienced by the globe, and the issue of environmental sustainability has become one of the most important issues of concern to business organizations, as among the most important causes are the scarcity of resources, the increasing degree of consumer awareness and the emergence of a new pattern of consumers looking to obtain products Green, healthy and environmentally friendly, which led to the need to find new production methods, including the adoption of green innovation, which has attracted the attention of many business organizations, due to its benefits that reflect positively on the environment and on achieving profitability; On this basis, organizations have tended to search for innovative ways that lead to the introduction of green products, the use of green processes and the creation of environmentally friendly regulatory practices, and thus expressing their orientation towards adopting environmental responsibility and achieving sustainability in it, by adopting and spreading a culture of green innovation to have an active role in expressing Adopting environmental responsibility and achieving outstanding environmental performance.
Bellakhdar، Messaouda . Green Innovation Is An Approach To Achieving Environmental Sustainability - With A Presentation Of Some Experiences. مجلة الاقتصاد والتنمية المستدامة.مج 05. العدد02. 2022/09/01 . جامعة الوادي [اكتب تاريخ الاطلاع] متاح على الرابط [انسخ رابط التحميل]
مقال
Keywords: Keywords: green innovation, green product, green process, environmental sustainability, presentation of experiences.